1983
DOI: 10.1111/j.1532-5415.1983.tb02202.x
|View full text |Cite
|
Sign up to set email alerts
|

The Elderly, Undernutrition, and Pharmacokinetics

Abstract: There is good evidence that malnutrition may alter the pharmacokinetic parameters and, thus, actions of several drugs. The elderly are probably most at risk, as malnutrition tends to affect factors already altered by primary and secondary aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 29 publications
2
2
1
Order By: Relevance
“…Consistent with our study, Bahat et al and Kara et al reported that chronic diseases increased the potential for inappropriate drug use in the elderly [40,41]. Furthermore, similar to our study, Sayın et al reported that polypharmacy increased potentially inappropriate drug use [42]. Another study reported no statistically significant relationship between the number of drugs used and potentially inappropriate drug use in hospitalized elderly patients [16].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with our study, Bahat et al and Kara et al reported that chronic diseases increased the potential for inappropriate drug use in the elderly [40,41]. Furthermore, similar to our study, Sayın et al reported that polypharmacy increased potentially inappropriate drug use [42]. Another study reported no statistically significant relationship between the number of drugs used and potentially inappropriate drug use in hospitalized elderly patients [16].…”
Section: Discussionsupporting
confidence: 91%
“…Other studies have reported similar results to ours [16,40]. However, Sayın et al reported that potentially inappropriate drug use was statistically more common in patients over 75 years of age [42]. The CCI score was not associated with potentially inappropriate drug use in our study, similar to the study by Martin et al [29].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Several fac-tors contribute to the nutritional status of the elderly, including poverty, aging, chronic disease, and chronic drug therapy. [24][25] Failure to take medication represents 50% or more of the incidences of noncompliance. Reasons for noncompliance range from conscious decisions or forgetfulness to financial restrictions.…”
Section: Nutritional Factorsmentioning
confidence: 99%
“…Long‐term administration of drugs to elderly with subclinical malnutrition can deplete the patient of specific nutrients, and the deficit may present in various ways (Table 8). 58 Malnutrition can alter the pharmacokinetics of many drugs 59 . Clearly, the elderly are more at risk for adverse and clinically important outcomes of drug‐nutrient and food‐drug interactions than are younger persons.…”
Section: Types and Mechanisms Of Interactionsmentioning
confidence: 99%